2023
DOI: 10.1371/journal.pmed.1004166
|View full text |Cite
|
Sign up to set email alerts
|

Essential childhood immunization in 43 low- and middle-income countries: Analysis of spatial trends and socioeconomic inequalities in vaccine coverage

Abstract: Background Globally, access to life-saving vaccines has improved considerably in the past 5 decades. However, progress has started to slow down and even reverse in recent years. Understanding subnational heterogeneities in essential child immunization will be critical for closing the global vaccination gap. Methods and findings We use vaccination information for over 220,000 children across 1,366 administrative regions in 43 low- and middle-income countries (LMICs) from the most recent Demographic and Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Therefore, the utilization of care continuity needs to be strengthened. A long distance to a health facility [ 50 ], the mother’s low education level [ 23 , 28 , 30 , 31 ], the partner’s low education level [ 48 ], less participation of women in decision-making [ 48 ], economic restrictions [ 24 , 26 29 ], and a lack of knowledge regarding ANC [ 51 ] prevent mothers from utilizing ANC. A delay in a first ANC visit also contributes to less frequency of ANC visits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the utilization of care continuity needs to be strengthened. A long distance to a health facility [ 50 ], the mother’s low education level [ 23 , 28 , 30 , 31 ], the partner’s low education level [ 48 ], less participation of women in decision-making [ 48 ], economic restrictions [ 24 , 26 29 ], and a lack of knowledge regarding ANC [ 51 ] prevent mothers from utilizing ANC. A delay in a first ANC visit also contributes to less frequency of ANC visits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this low percentage in our study suggested that health care providers did not sufficiently educate mothers on the importance of delivery with an SBA during ANC. There are also other reasons why women avoid delivery with an SBA or institutional delivery, such as economic restrictions [ 24 , 26 29 ] and a long distance to a health facility [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the population level, analyses of the spatial overlap between gaps in immunization coverage and other health services can complement these individual-level analyses. Spatial analyses conducted in recent years have emphasized the substantial degree of subnational inequality in vaccine coverage [13,[17][18][19][20][21][22][23], as well as other key health services and indicators [22,[24][25][26][27][28][29][30][31]. Fewer studies have assessed whether subnational distributions of zero-dose (or no-DTP) children are similar to those for other health indicators [32].…”
Section: Introductionmentioning
confidence: 99%
“…With a population of 1,233,760 residents overall, the area struggles with health and educational inadequacies that may affect vaccination rates. These challenges are compounded by socioeconomic inequalities since children from economically disadvantaged homes have a much lower likelihood of receiving complete immunization [9].…”
Section: Introductionmentioning
confidence: 99%